Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2018)
Descemet's Membrane Endothelial Keratoplasty: Clinical Results of Single Versus Triple Procedures (Combined With Cataract Surgery) Chaurasia S, Price FW, Gunderson l, Price MO. Ophthalmology 2014; 121: 454-8. Management and Outcome of Retinoblastoma with Vitreous Seeds Manjandavida FP, Honavar SG, Reddy VAP, Khanna R. Ophthalmology 2014; 121, 517-24. Cost – Effectiveness of Femtosecond Laser – Assisted Cataract Surgery versus Phacoemulsification Cataract Surgery Affiliations Abell RG, Vote BJ Ophthalmology 2014; 121: 10-6. Intravitreal Aflibercept Injection for Macular Edema Resulting from Central Retinal Vein Occlusion Korobelnik JF, Holz FG, Roider J, Ogura Y, Simader C, Schmidt – Erfurth U, Lorenz K, Honda M, Vitti R, Berliner AJ, Hiemeyer F, Stemper B, Zeitz O, Sandbrink R. Ophthalmology 2014; 121: 202-8.